The Implementation of Bentengan Games to Improve Agility and Coordination in Primary School Students - Sufi, Ali; Dinata, Vega Candra; Maslikah, Siti (SPORT-Mu: Jurnal Pendidikan Olahraga, 2024)
This research examines the application of the traditional game "Bentengan" in sports learning to improve the agility and coordination of grade III elementary school students at SDN Petemon Surabaya. The method used was Classroom Action Research (PTK) with 30 students as subjects. Pre-cycle results show that only 20% of students reached the Minimum Completion Criteria (KKM). However, after implementing the game in cycle I, there was a significant increase, with 50% of students reaching the KKM, and in cycle II, this figure increased to 93.4%. This research not only shows progress in students' physical skills, but also an increase in their enthusiasm and engagement. These findings emphasize the importance of integrating traditional games into the physical education curriculum to create a positive and effective learning atmosphere, and provide recommendations for educators to apply this method more widely in sports learning in elementary schools.Keywords : fortification, agility, coordination